Essential oil of Pulicaria vulgaris (prostrata) and its biological activity - Zhanzhaxina, A.Sh.; Suleimen, Ye.M.; Ishmuratova, M.Yu.; Iskakova, Zh.B.; Seilkhanov, T.M.; Birimzhanova, D.A.; Suleimen, R.N. (KSU Publ., 2020)
The investigation of the chemical composition, antioxidant and cytotoxic activities of the essential oil of Pulicaria vulgaris wild growing in Akmola region, Kazakhstan was the aim of the study. The essential oil was obtained by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC/MS). A total of 49 compounds were identified representing 86.4 % and the major components were patchoulane (37.4%), buddledin C (13.9 %), T-cadinol (4.7 %), trans-sesquisabinene hydrate (4.1 %), dyhydro-β-agarofuran (2.7 %), (Z)-α-atlantone (1.8 %) and corymbolone (1.2 %). Six components were identified as unknown (2.6 %). The antioxidant activity was evaluated by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and the essential oil demonstrated an average scavenging effect at 0.75 and 1 mg/ml concentrations compared with butylhydroxyanisole (BHA). The antiradical activity results of the P. vulgaris essential oil is published for the first time. Cytotoxic activity assay was studied against Artemia salina larvae and it can be concluded that the essential oil has a good lethal toxicity in all tested concentrations (10–1 mg/ml). The authors attribute this result to the presence of the patchoulane as a major component, which is known for its activity against ovarian cancer cells.
Pulicaria vulgaris (prostrata) эфир майы жəне оның биологиялық белсенділігі
Эфирное масло Pulicaria vulgaris (prostrata) и его биологическая активность
Keywords: Pulicaria vulgaris (prostrata); essential oil; water distillation; GC/MS; patchoulane; antioxidant; cytotoxic activities